Smart home automation system air conditioning - Muhammad Asnawi Bin Mohd Ariffin (School of Microelectronics, University Malaysia Perlis, 2015)
This project is about a system that power on/off the air conditioner automatically in term of sensor. This system is developed to replace the traditional way by control the air conditioner using remote. The use of this traditional system is time consuming as the people need to power on and off manually. It will take more time when that people forgot to switch off instantly after going out. Therefore, this project uses passive infrared (PIR) sensor to detect the movement of the people that enter or exit the room. The objective of this project is to reduce time to switch on/off the air-conditioner inside the room without using remote control and to reduce electric cost bill upon for the long time usage for a certain time. This system requires two PIR sensors, a microcontroller (Arduino UNO) and USB fan. The signal receive is stored in Arduino and trigger the transistor as switch in order to switch on or off. This system will speed things up our life easier.